STEM-22. TARGETING PYRIMIDINE SYNTHESIS ACCENTUATES MOLECULAR THERAPY RESPONSE IN GLIOBLASTOMA STEM CELLS. (11th November 2019) - Yang, Kailin; Wang, Xiuxing; Wu, Qiulian; Kim, Leo; Morton, Andrew; Gimple, Ryan; Prager, Briana; Shi, Yu; Zhou, Wenchao; Bhargava, Shruti; Zhu, Zhe; Jiang, Li; et al.
Abstract: Glioblastoma stem cells (GSCs) reprogram glucose metabolism by hijacking high-affinity glucose uptake to survive in a nutritionally dynamic microenvironment. Here, we trace metabolic aberrations in GSCs to link core genetic mutations in glioblastoma to dependency on de novo pyrimidine synthesis. Targeting the pyrimidine synthetic rate-limiting step enzyme carbamoyl-phosphate synthetase 2, aspartate transcarbamyolase, dihydroorotase (CAD) or the critical downstream enzyme, dihydroorotate dehydrogenase (DHODH) inhibited GSC survival, self-renewal, and in vivo tumor initiation through the depletion of the pyrimidine nucleotide supply in rodent models. Mutations in EGFR or PTEN generated distinct CAD phosphorylation patterns to activate carbon influx through pyrimidine synthesis. Simultaneous abrogation of tumor-specific driver mutations and DHODH activity with clinically approved inhibitors demonstrated sustained inhibition of metabolic activity of pyrimidine synthesis and GSC tumorigenic capacity. Higher expression of pyrimidine synthesis genes portend poor prognosis of glioblastoma patients. Collectively, our results demonstrate a therapeutic approach of precision medicine through targeting the nexus between driver mutations and metabolic reprogramming in cancer stem cells.